Feeding and managing early lactation cows - James R. Dunham (Kansas Agricultural Experiment Station Research Reports, 1987)
Feeding and managing dairy cows during the prepartum and early lactation periods have more effect on total lactation yields than all other factors. It is during this time that the pattern of milk production is established for the entire lactation. The full production potential of high producing cows cannot be realized unless these periods are given special consideration.; Dairy Day, 1987, Kansas State University, Manhattan, KS, 1987;
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-114-S; Report of progress (Kansas Agricultural Experiment Station); 527; Dairy; Lactation; Protein; Production; Performance